Effect of solvent types on the physical properties of tannin-phenol formaldehyde adhesive - Lixia, Heather Mah (2017)
The main objective of this study was to determine the effect of solvents and types of Acacia mearnsii tannin on the physical properties of tannin phenol formaldehyde (TPF) resin. In this study, two types of tannins (Australia and Italy) at three ratios (20%, 30% and 40%) of tannin solution with five types of solvents (distilled water, ethanol, sodium sulphate, methanol and glycerol) were used. The tannin solution was mixed with commercial phenol formaldehyde (PF) resin to produce TPF resin. Meanwhile commercial PF resin was used as control. The results showed that, TPF resin using both types of tannin have similar trend of pH, viscosity, solid content and gel time when any types of solvent were used. Generally, as the tannin ratio increased, the pH and solid content decreased, gel time shorter and viscosity increased in any types of solvents. Findings show that the tannin of Italy has better water resistance compared to Australia tannin. Apart of distilled water, TPF consists of other solvents had higher viscosity compared to distilled water. Glycerol offers fast gel time, highest viscosity and solid contents properties of TPF resin.